Comparison of Students' Chemistry Learning Outcomes through Verification of Concept Maps and Mind Maps in Discovery Model Learning - Auliah, Army; Islawati, Islawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
Chemistry learning requires an understanding of complex abstract concepts. The Discovery Learning model has been applied to improve student understanding, but the verification stage in this model is often an obstacle in connecting the concepts found. This study compares the verification of concept maps and mind maps in improving student learning outcomes. The research method used is comparative descriptive, with two experimental groups each using concept maps and mind maps. The research instruments include learning outcome tests, assessment rubrics, and observations. The results showed that concept maps support systematic understanding more, while mind maps are more effective in developing flexibility of thinking. The verification process plays a role in correcting student misconceptions. These findings provide insight for educators to adjust learning methods to improve understanding of chemical concepts.